Recent advances and future prospects in knowledge, information and creativity support systems : selected revised papers from the tenth International Conference on Knowledge, Information and Creativity Support Systems (KICSS 2015), 12-14 November 2015, Phuket, Thailand /: selected revised papers from the tenth International Conference on Knowledge, Information and Creativity Support Systems (KICSS 2015), 12-14 November 2015, Phuket, Thailand. (2018) - Unknown
No abstract available